AI and the Future of Healthcare Work: Human-AI Collaboration in Medical Practice - Bhavyateja Potineni (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of artificial intelligence on healthcare workforce dynamics, exploring the dual pathways of automation and augmentation in medical practice. It analyzes how AI technologies are reshaping healthcare delivery across administrative, diagnostic, and clinical domains while identifying evolving professional competencies required in an AI-integrated environment. The discussion encompasses the differential displacement risks across healthcare professions, frameworks for effective workforce transition, and strategies for maintaining appropriate human oversight. The article further addresses educational adaptation needs for healthcare professionals and proposes policy imperatives to balance technological efficiency with professional wellbeing. Throughout, the article emphasizes that successful AI integration in healthcare depends not merely on technological implementation but on thoughtful workforce planning that preserves the human element in medicine while leveraging AI’s capabilities to enhance healthcare delivery and outcomes.